Assessment of lightning protection system in building / Stephanie Simson - Stephanie, Simson (Faculty of Architecture, Planning and Surveying, 2013)
Protection is the condition of being protected against danger, loss, or damages. In the general sense, protection is a concept to kept safe and comfort. Lightning protection systems are used to prevent or lessen damage to structures done by lightning strikes. Lightning protection systems mitigate the fire hazard which lightning strikes pose to structures. A lightning protection system provides a low-impedance path for the lightning current to lessen the heating effect of current flowing through flammable structural materials. A research was conducted on government public buildings; Sultan Abdul Aziz Royal Gallery, Raja Tun Uda Library, Sultan Salahuddin Abdul Aziz Mosque, and Sultan Alam Shah Museum located in Shah Alam and Klang. The purpose of this research is to determine the Lightning Protection System used in the building. In research methodology, observation and through interview will be the tools for collecting data. Besides that, the journals, books, thesis, and catalogues also used as a tools for collecting data.Finally, the research ends with the conclusion and recommendation chapter. This is for conclude and summarize the whole chapter and conclude the result/finding/analysis in chapter 5, whether the objectives, or aims of this research is achieves or not.